2020
DOI: 10.1111/cdev.13425
|View full text |Cite
|
Sign up to set email alerts
|

The Developing Bodily Self: How Posture Constrains Body Representation in Childhood

Abstract: Adults’ body representation is constrained by multisensory information and knowledge of the body such as its possible postures. This study (N = 180) tested for similar constraints in children. Using the rubber hand illusion with adults and 6‐ to 7‐year olds, we measured proprioceptive drift (an index of hand localization) and ratings of felt hand ownership. The fake hand was either congruent or incongruent with the participant’s own. Across ages, congruency of posture and visual–tactile congruency yielded grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(158 reference statements)
3
6
1
Order By: Relevance
“…Specifically, responses decreased in the asynchronous condition. This contrasts with previous studies of the rubber hand illusion which revealed adult-like differences between synchronous and asynchronous conditions from 4 years 6 , 8 . Because the present study used identical questions and prompts to these previous studies, and because children of this age give very low ratings to control questions 7 , 32 , we argue strongly against explaining this result simply as a tendency for children of this age to avoid saying ‘no’.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Specifically, responses decreased in the asynchronous condition. This contrasts with previous studies of the rubber hand illusion which revealed adult-like differences between synchronous and asynchronous conditions from 4 years 6 , 8 . Because the present study used identical questions and prompts to these previous studies, and because children of this age give very low ratings to control questions 7 , 32 , we argue strongly against explaining this result simply as a tendency for children of this age to avoid saying ‘no’.…”
Section: Discussioncontrasting
confidence: 99%
“…The second result we found unrelated to hand size was that, as predicted, there were consistent effects of visuotactile synchrony across ownership, touch referral and drift measures. The present study complements existing literature on the importance of touch for children as well as adults 5 , 6 , 8 – 10 , 30 , 31 , and adds to the growing movement to incorporate haptics as an essential element of virtually-controllable avatars. However, these effects of visuotactile synchrony were not consistent with age: in fact for touch referral and ownership, the role of synchrony grew with age.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The rear-search errors may have been caused by a misalignment of the real body and the mark owing to the priority given to the visible mirrored body. The tendency for children to prioritize the processing of the visible body in multisensory processing was also reported in a study of RHI among 6-to 7-yearold children, suggesting that integrated processing of vision, touch, and proprioception may require a lot of time (Gottwald et al, 2021). However, RHI among younger children is considered difficult to comprehensively examine owing to the nature of the task, which requires verbal skills for subjective reports and fine motor control that indicates proprioceptive drift (Cowie et al, 2013(Cowie et al, , 2016.…”
Section: Introductionmentioning
confidence: 73%